Guidance for Processing Cured and Smoked Ham and Pork Loins in Retail Operations - Keith R. Schneider; Victor Garrido; W. Steve Otwell; Ray Mobley (EDIS)
This recommended guidance is for specialty meat products processed at retail, for display and distribution at retail. This document is FSHN05-07, one of a series of the Food Science and Human Nutrition Department, Florida Cooperative Extension Service, IFAS, University of Florida, Gainesville, FL 32611. Published: February 2005.